Nationwide changes in physical activity, nutrient intake, and obesity in South Korea during the COVID-19 pandemic era - Yang, Hong Jun; Park, Saengryeol; Yoon, Tai-Young; Ryoo, Jae-Hong; Park, Sung Keun; Jung, Ju Young; Lee, Ju-Hyung; Oh, Chang-Mo (Frontiers in Endocrinology, 2022)
Background This study aimed to examine changes in obesity rates and obesity-related factors during the COVID-19 pandemic compared to a previous period. Methods An ecological time-series study was designed using the Korean National Health and Nutritional Examination Survey (KNHANES) database from 2014 to 2020. The expected values of obesity rate, physical activity rate, and nutrient intake for 2020 were estimated. The differences between the predicted and actual values for 2020 were also examined. In addition, a multiple logistic regression model was used to examine the changes in obesity and physical activity rates in 2020 compared to 2019. Results The actual obesity rates in 2020 were higher, and the walking and aerobic physical activity rates were lower than the predicted values for the same year. However, the actual resistance training rates in 2020 were higher and the total energy intake was lower than the predicted values for 2020. In the multiple logistic regression model, the odds ratios for obesity, aerobic physical activity, and walking among men in 2020 were 1.29 (95% CI: 1.08 to 1.55), 0.86 (0.74 to 1.01), and 0.84 (0.73 to 0.97), respectively, compared to those in 2019. However, there were no significant differences between the values for women in 2020 and 2019. Conclusions This study suggests that the male obesity rate in Korea has significantly increased during the COVID-19 epidemic, mainly due to a decrease in physical activity.